Clinical Management of Sarcoptic Mange in Rabbits - Shakya, Mukesh; Singh, Mamta; Jayraw, AK; Saini, Vijesh (Indian Journal of Veterinary Sciences and Biotechnology, 2018)
Dermatological problems are one of the most common clinical entities in domestic pets and fur bearing animals (Deshmukh et al., 2010). Amongst them, sarcoptic mange is one of the most common and major constraint in commercial rabbit production in India (Darzi et al., 2007). Sarcoptic mange is the most obstinate, resistant and contagious disease with zoonotic importance (Kumar et al., 2002). It is mainly characterized by pruritis, alopecia and in prolonged illness; the animal becomes emaciated and may even die due to cachexia (Roy et al., 2001). Being a contagious parasitic skin disease, mites are generally spread by direct contact between infected and healthy rabbits (Panigrahi and Gupta, 2013). Sarcoptic mange, if left untreated may cause significant morbidity and economic loss in the livestock. Moreover, high costs are associated with acaricides used in infested livestock (Rehbein et al., 2003 and Walton et al., 2004). The avermectin compounds can be used to treat rabbits which are naturally infected with scabies (Kachhawa et al., 2013 and Eraslan et al., 2010). The present communication reports the successful